Public Perception and Participation in Environmental Preservation of Watershed - Andi Bustan (Hasanuddin University, 2016)
Environmental aspects have been some of the most argued about topics in society, including the role of the government as a stakeholder. Deforestation and illegal mining have been destroying the many ecosystems and rainforest habitats, including along the Katingan Watershed. The research objective is to describe public perception and participation in environmental preservation. The research used descriptive qualitative method and applying Spradley Domain Analysis. Primary and secondary data were obtained directly from field informants using interviews, observations and documentation. The research results show that the people’s perception and participation in environmental preservation was categorized into two groups. The first group one stated that they did contributed out of personal and financial interests, whilst the second groups were simply following the instructions of the government and local leaders. In general, locals have different perception on how they utilize the natural resources. The management of natural resources was perceived as being done for economic reasons, with the assumption that it were used sustainably. People’s involvement in preserving nature were affected their own needs either individually or collectively. Participation of the people in the conservation around the watersheds area was done for reasons of individual desire, solidarity, and to follow instructions from the government and Katingan Hilir leader. Environmental effort is carried out in activities aiming to protect and prevent damage to the area of the Katingan River. This lead to argue that diverse people’s perception to preserving environment generates the difference participation in their awareness.